PEMANFAATAN AKUN TIKTOK @JAYFUJIWARA SEBAGAI MEDIA PEMBELAJARAN BAHASA INGGRIS BAGI PEMBELAJAR BAHASA ASING DI ERA DIGITAL - Anita Agustina Wulandari; Mochammad Arkansyah; Deassy Ratna Juwita Sari (Jurnal Spektrum Komunikasi, 2025)
The advancement of digital technology in the contemporary era like today has brought major changes in various aspects of human life including education. In recent years, TikTok is one of the online platforms that has grown rapidly. This application is not only an entertainment platform but has also developed into a learning platform because of its creative and interesting content. Although TikTok has become popular as an entertainment platform, now many accounts use it as a learning platform such as learning a foreign language. A famous account in this field is @jayfujiwara who creates educational content to teach English with 5.9 million latest followers. Considering this phenomenon, this study will investigate how the TikTok account @jayfujiwara is used as a medium for learning English, as well as how effective and impactful the content on the account is on students learning a foreign language. After this study was conducted, it can be concluded that the TikTok account @jayfujiwara is an innovative and flexible English learning medium in the modern era. The real impacts experienced by students include increasing their motivation to learn and improving better speaking and listening skills, practical application of English, reducing their anxiety while learning, and strengthening their community networks. Therefore, social media platforms, especially TikTok, can help students learn English, especially the younger generation who are familiar with digital technology.